Cold water [videorecording (DVD)] - Assayas, Olivier; Assayas, Olivier; Ledoyen, Virginie, 1976-; Fouquet, Cyprien; Szabó, László, 1936- (Criterion collection, 2018)
Follows the angst of teenage lovers Gilles and Christine as they rebel against family and society.